Effect of life skills building education and micronutrient supplements provided from preconception versus the standard of care on low birth weight births among adolescent and young Pakistani women (15-24 years): a prospective, population-based cluster-randomized trial - Jo-Anna B. Baxter; Yaqub Wasan; Sajid B. Soofi; Zamir Suhag; Zulfiqar A. Bhutta (BMC, 2018)
Abstract Background Risk factors known to impact maternal and newborn nutrition and health can exist from adolescence. If an undernourished adolescent girl becomes pregnant, her own health and pregnancy are at an increased risk for adverse outcomes. Offering preconception care from adolescence could provide an opportunity for health and nutrition promotion to improve one's own well-being, as well as future pregnancy outcomes and the health of the next generation. Methods The Matiari emPowerment and Preconception Supplementation (MaPPS) Trial is a population-based two-arm, cluster-randomized, controlled trial of life skills building education and multiple micronutrient supplementation provided in a programmatic context to evaluate the impact on pre-identified nutrition and health outcomes among adolescent and young women (15-24 years) in Matiari district Pakistan, and the infants born to them within the context of the trial. The primary aim is to assess the effect of the intervention on the prevalence of low birth weight births (< 2500 g). The intervention includes bi-monthly life skills building education provided from preconception, and supplementation with multiple micronutrients during preconception (twice-weekly), pregnancy (daily), and post-partum (daily to 6 months). The standard of care includes non-regulated community-based health sessions and daily iron and folic acid supplementation during pregnancy. Additional outcome information will also be collected at set time periods. Among participants, these relate to nutrition (anthropometry, nutritional status), morbidity, and mortality. Among infants, these include birth outcomes (stillbirth, preterm birth, length of gestation, small for gestational age, birth defects), anthropometry, morbidity, and mortality. Discussion Preconception care from adolescence that includes interventions targeting life skills development and nutrition is suggested to be important to improving the health and nutrition of adolescent and young women and their future offspring. This study is expected to offer insight into providing such an intervention both within a programmatic context and with an extended exposure period prior to conception. Trial registration The MaPPS Trial was registered retrospectively on clinicaltrials.gov (Identifier: NCT03287882) on September 19, 2017.